2023
DOI: 10.1021/jacs.3c05866
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-/Mechano-Chromic Chiral Coordination Dimer: Formation of Switchable and Metastable Discrete Structure through Chiral Self-Sorting

Kazuyoshi Takimoto,
Takumi Shimada,
Kazuhiko Nagura
et al.

Abstract: Although strong chiral self-sorting often emerges in extended covalent or supramolecular polymers, the phenomenon is generally weak in discrete assemblies (e.g., dimers and oligomers) of small molecules due to the lack of a cooperative growth mechanism. Consequently, chiral self-sorting has been overlooked in the design of switchable and metastable discrete supramolecular structures. Here, we report a butyl-benzo[h]quinoline-based iridium(III) complex (Bu-Ir) with helical chirality at its metal center, which f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Würthner and co‐workers reported that the core‐twisted perylene bisimide self‐assembled into homochiral one‐dimensional (1D) fibers and heterochiral two‐dimensional lamellar liquid crystals under different cooling rates of the monomer solution, which exhibited completely distinctive absorption properties [8] . Recently, Takimoto et al [9] . demonstrated a thermo‐/mechano‐chromism originating from the monomer and homochiral dimer transformation of a helical chiral iridium(III) complex, thus realizing switchable chiral supramolecular polymerization with naked‐eye visualization.…”
Section: Introductionmentioning
confidence: 99%
“…Würthner and co‐workers reported that the core‐twisted perylene bisimide self‐assembled into homochiral one‐dimensional (1D) fibers and heterochiral two‐dimensional lamellar liquid crystals under different cooling rates of the monomer solution, which exhibited completely distinctive absorption properties [8] . Recently, Takimoto et al [9] . demonstrated a thermo‐/mechano‐chromism originating from the monomer and homochiral dimer transformation of a helical chiral iridium(III) complex, thus realizing switchable chiral supramolecular polymerization with naked‐eye visualization.…”
Section: Introductionmentioning
confidence: 99%
“…Würthner and coworkers reported that the core-twisted perylene bisimide self-assembled into homochiral one-dimensional (1D) fibers and heterochiral two-dimensional lamellar liquid crystals under different cooling rates of the monomer solution, which exhibited completely distinctive absorption properties. [8] Recently, Takimoto et al [9] demonstrated a thermo-/mechano-chromism originating from the monomer and homochiral dimer transformation of a helical chiral iridium(III) complex, thus realizing switchable chiral supramolecular polymerization with naked-eye visualization.…”
Section: Introductionmentioning
confidence: 99%